Hand Doll Model in Teaching Speaking Skill - Moh. Hafidz (SELL Journal : Scope of English Language Teaching, Linguistics, and Literature, 2016)
Teaching speaking skill is a systematical process of sending message orally. The aim of this result is describe the use of Hand Doll model in teaching Speaking Skill at junior high school. The researcher uses qualitative descriptive in case study design. Researcher uses some instruments such as checklist, interview and documentation. The result of this research is the Han doll model is implemented well and motivates students to speak English easily in simple dialogue such as daily topics. The instructors control the class to know the student’s problems such as pronunciation, vocabulary and comprehension. Then, reflecting those problems in modelling performance in front of the class.